SISTEM PAKAR SKRINING PENYAKIT YANG DISEBABKAN OLEH VIRUS MENGGUNAKAN CERTAINTY FACTOR: SISTEM PAKAR SKRINING PENYAKIT YANG DISEBABKAN OLEH VIRUS MENGGUNAKAN CERTAINTY FACTOR - Made Hanindia Prami Swari; I Gusti Ngurah Agung Mahendra (Institute of Computer Science (IOCS), 2019)
Extraordinary event is the emergence or increasing sickness or death epidemiologically in an area and in certain time and can lead towards plague. In addition to contagious diseases, there are also some other cause of extraordinary event such as diseases and poisoning. The lack of information regarding the diseases which is caused by virus can make extraordinary event hard to be prevented. Early detection can help people to get information about the disease so they can do medication and early prevention. A Master system is a tool to assist in early detection for disease caused by virus. A master system is an artificial intelligence (AI) program which combines knowledge base with inference system. In drawing the conclusion, the master system is using Certainty Factor. In designing the system consist of designing context diagram and DFD and the next development is implementing programming language PHP and the last stage of the system development is the Black Box Testing. The result of the research is the master system that is able to identified 7 diseases. The output system is the disease completed with the result of the patient’s trust score which is counted using certainty factor, disease definition, disease prevention and solution.